Effect of SiC Powder Additive on Mechanical Properties of Al-Pb Alloy Produced by Mechanical Alloying - Hussein, Suhair G.; Abood, Adnan N.; Sahib, Nabeel Kadim Abdel (Al-Nahrain Journal for Engineering Sciences, 2018)
One of the major usages for Al–Pb alloy are bearing alloys because of its lubricant behavior of Pb phase component. Applications of these alloys are in heavy duty, such as boring mills, presses, lathes, milling machines and hydraulic pump bushings. In present work, SiC powder was selected as additive for improving the mechanical properties of Al-Pb alloy that produced by mechanical alloying method. The percentage weight of SiC powder are (2.5, 5,10, 15 %) which mixing together with Al- Pb alloy for two hours in ball milling device, then compacted and sintering to obtain the improved alloy, and examine the mechanical properties (compressive strength and microhardness) of produced alloy. Results show that the additive of SiC powder on the Al-Pb alloy lead to improve the microhardness which increased with increased the percentage of additive, in the other hand, the compressive strength had a reverse effective with increased the percentage of SiC powder.